2006
DOI: 10.1037/0022-0167.53.4.543
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic perfectionism as a predictor of relationship continuity and distress among college students.

Abstract: This study examined the nature and impact of dyadic perfectionism over a 3-month interval within a sample of 116 college students who were currently involved in an intimate heterosexual relationship. Dyadic perfectionism scores were stable and correlated as expected with scores on concurrent measures of adult attachment orientations and relationship satisfaction. Logistic regression analyses revealed that, controlling for initial commitment status and adult attachment orientations, Time 1 dyadic perfectionism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
2
28
0
3
Order By: Relevance
“…Taken together, the findings from the four studies (Habke et al, 1999;Haring et al, 2003;Lopez et al, 2006;Shea et al, 2006) provide evidence that both partner-oriented perfectionism and partner-prescribed perfectionism have negative effects on relationship quality. Still, there remain questions.…”
Section: Open Questionsmentioning
confidence: 95%
See 3 more Smart Citations
“…Taken together, the findings from the four studies (Habke et al, 1999;Haring et al, 2003;Lopez et al, 2006;Shea et al, 2006) provide evidence that both partner-oriented perfectionism and partner-prescribed perfectionism have negative effects on relationship quality. Still, there remain questions.…”
Section: Open Questionsmentioning
confidence: 95%
“…First, the evidence that dyadic perfectionism has negative effects is limited to married couples (Habke et al, 1999;Haring et al, 2003). In university students, negative effects have been found only for the discrepancy aspect of partner-oriented perfectionism (Lopez et al, 2006;Shea et al, 2006). Consequently, it is unclear what effects partner-prescribed perfectionism has in students' romantic relationships, particularly as romantic relationships in students have shown a number of significant differences (e.g., more commitment problems) compared to those in married couples (Hsueh, Morrison, & Doss, 2009;Punyanunt-Carter, 2004).…”
Section: Open Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In married couples, partner-oriented perfectionism did not show any significant relationships with relationship satisfaction, marital happiness, dyadic adjustment, or sexual satisfaction (Habke et al, 1999;Haring et al, 2003). In university students, however, partner-oriented perfectionism showed both positive and negative relationships: Two studies found partner-oriented perfectionism to show positive correlations with relationship satisfaction (Lopez, Fons-Scheyd, Morúa, & Chaliman, 2006;Shea, Slaney & Rice, 2006) whereas one study found negative correlations with relationship satisfaction and longterm commitment (Stoeber, 2012). Hence, like other-oriented perfectionism, partner-oriented perfectionism seems to be an ambivalent form of perfectionism associated with both adjustment and maladjustment.…”
Section: Dyadic Perfectionismmentioning
confidence: 99%